A Venturini based modulation technique for a new isolated AC/AC power converter - Nasir, Usman; Rivera, Marco; Costabeber, Alessando; Wheeler, Patrick (2016)
The Future Global Electricity Network is expected to have large integration of renewable generators, and to be widely interconnected. As a consequence, the multi-modular bidirectional AC/AC power conversion architectures will play a major role in improving power flow controllability, power quality and availability. This paper proposes a new power converter topology suitable for AC/AC conversion in medium and high voltage applications, based on the matrix concept. The proposed topology combines the advantages of matrix converters with those of modular converters, providing high modularity and scalability, reduced weight and volume, minimum number of conversion stages and minimum energy storage. Galvanic isolation is provided at medium frequency, reducing size and cost of the transformer. The paper introduces the converter concept and commutation strategy and proposes a modified Venturini modulation in order to provide a per-switching cycle control of the Volt-Second balance across the transformer.